(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate Serum Lipid Profile in preeclampsia Patients and normal pregnant women in Mirpur, AJK. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology and Biochemistry, Mohtarma Benazir Bhutto Shaheed Medical College Mirpur AJK from January 2018 to July 2019. Materials and Methods: We take for study 200 Preeclampsia patients and 100 health pregnant women. We take blood samples from both groups women and analyzed the samples on Microlab 300 for serum lipid profile. (Cholestol, HDL, LDL, VLDL and Triglyceride). For the study we use kits made of Merck Pvt. We also did other biochemistry test and hematological test. Results: The result indicate that all the lipid profile (LDL, Triglyceride) is higher except HDL in women with as compare to normal pregnant women. Total cholesterol (254.5 ± 12.8) mg/dl, LDL (128.9 ± 21.5) mg/dl, and Triglyceride (199.2 ± 32.5) mg/dl, in Preeclampsia are higher as compare to normal pregnant women. While HDL (40.77± 8.5) mg/dl, is decreased in Preeclampsia as compare to normal pregnant women. Conclusion: The result of this study it is conclude that pregnant women should adopt balanced diet and reduced the lipid profile and reduced their weight and change their life style and adopt healthy life style.